(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Despite advances reducing pancreaticoduodenectomy (PD) mortality to <5%, postoperative pancreatic fistula (POPF) remains a leading source of morbidity. Roux-en-Y pancreaticojejunal reconstruction (RYPJ) has been proposed to divert bile and lower PF risk, but direct comparisons with conventional continuous loop anastomosis (CPJ) are scarce. Methods: In this single-center retrospective study (2020–2024), we reviewed 108 PDs data out of 130 total cases performed. Patients were grouped by reconstruction type: RYPJ (n=53) versus CPJ (n=55). All underwent duct-to-mucosa pancreatojejunostomies. Primary endpoint was ISGPF-defined POPF rate; secondary endpoints included overall morbidity, operative time, estimated blood loss, length of stay, incidence of delayed gastric emptying and 30-day mortality. Results: Baseline demographics, tumor characteristics, pancreatic duct diameter, and gland texture were comparable. PF occurred in 11 patients (10.2%): 5/53 (9.4%) IPJ versus 6/55 (10.9%) CPJ (p=0.800). Overall morbidity was 32/108 (29.6%) (IPJ 32% vs CPJ 27.3%, p=0.674). Operative mortality was 3.7% in both groups (p=1.000). Mean blood loss did not differ (350 mL vs 330 mL, p=0.780). IPJ added 72 minutes to OR time (442 ± 32 min vs 370 ± 38 min, p=0.005) without shortening hospital stay (9.5 ± 5.0 d vs 10.1 ± 3.7 d, p=0.483). Conclusion: Isolated Roux-en-Y reconstruction prolongs operative time but does not reduce PF, morbidity, or mortality compared with single-loop CPJ. Routine use of IPJ after PD is not supported by these findings.